The Moderating Role of Retention Factor on The Relationship Between Career Adaptability and Organizational Commitment - Igbomor, Emmanuel (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: There is increase in competition among manufacturing companies in Nigeria as a result of rapid changes in the business domain. These changes in the business domain account for the reason why ever companies in the manufacturing sector are interested in having employees that can cope and adapt to changes and also committed to the goals and objective of the organization. This study aims to examine the moderating role of retention factors (compensation) on the relationship between career adaptability and organizational commitment in the manufacturing sector in Nigeria. Methodology: A survey was carried out in this study and one hundred and fourteen (100) questionnaire were administered to the respondents out of which eighty two (82) were fully retrieved and completed. Data obtained from the respondents were analyzed by means of descriptive (Cronbach Alpha, Mean and standard deviation) and inferential (Structural Equation Modeling (SEM) statistical techniques. While hierarchical regression was used to analyze and validate the moderating effect of retention factor on the relationship between career adaptability and organization commitment. Findings: The findings of the study revealed that the effect of career adaptability on organizational commitment is not significant while the effect of career adaptability on retention factor is significant. It was also found that they is no direct effect between retention factor and organizational commitment. Finally, it was confirmed that retention factor has a moderating effect on the link between career adaptability and organizational commitment. Conclusion: Implementation of career development programs and providing opportunities for continuous learning makes top talented employee remain in the organization. And also, employment of retention factors, particularly compensation enhances the commitment of the employees towards the organization.